2011
DOI: 10.1542/peds.2010-3109
|View full text |Cite
|
Sign up to set email alerts
|

Premasticating Food for Weaning African Infants: A Possible Vehicle for Transmission of HIV

Abstract: Counselors and caregivers should be aware of the adverse effects of premastication. Education should include advice to avoid premastication and to seek health advice for oral conditions in the caregiver and child. More studies are needed to better define the extent and risks of premastication, including its possible role in increasing HIV-1 transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 37 publications
0
13
1
Order By: Relevance
“…Though not considered a common mode of transmission [53], [54], and despite reports of antiviral activity of salivary components [55], relatively higher HIV RNA in saliva of women may represent unique, sex-dependent transmission risk associated with saliva; the transmission risk associated with oral-sex is low and still controversial. Such findings may have implications for HIV transmission in special circumstances, such as high viral replication and mandates further investigation [46], [56], [57], [58].…”
Section: Discussionmentioning
confidence: 99%
“…Though not considered a common mode of transmission [53], [54], and despite reports of antiviral activity of salivary components [55], relatively higher HIV RNA in saliva of women may represent unique, sex-dependent transmission risk associated with saliva; the transmission risk associated with oral-sex is low and still controversial. Such findings may have implications for HIV transmission in special circumstances, such as high viral replication and mandates further investigation [46], [56], [57], [58].…”
Section: Discussionmentioning
confidence: 99%
“…Beginning as early as one month of age and continuing for two years or more, the practice has been reported in nearly a third of 119 traditional societies surveyed in ethnographic literature (Pelto, Zhang & Habicht, 2010), and is still practiced across diverse societies today (e.g., China (Pelto, Zhang & Habicht, 2010), South Africa (Maritz, Kidd & Cotton, 2011)). Premasticating mechanically processes, lubricates, and adds salivary amylase to foods, facilitating digestion and absorption (Humphrey & Williamson, 2001) As such, the practice may have been favored throughout much of human evolution to enhance nutritional availability of weaning foods (Pelto, Zhang & Habicht, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…(Hesselmar et al, 2013). Conversely, others have raised concerns that premastication may transfer HIV (Maritz, Kidd & Cotton, 2011; Gaur et al, 2009) and bacteria with cariogenic or pathogenic potential, including group A streptococcus (Steinkuller, Chan & Rinehouse, 1992) and Streptococcus mutans (Berkowitz, Turner & Green, 1981). …”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6] Martiz and colleagues 6 from South Africa reported that markers of disrupted oral mucosal integrity and presence of blood in the mouth were frequently seen in the person who prechews and the child who receives prechewed food.…”
mentioning
confidence: 99%
“…2,5,6,11 While the role and potential benefits of these practices have been previously summarized, 11 research supporting them is lacking. The burden is on healthcare providers to review individualized risk-benefit-based counseling in the context of the country and culture in which they work and account for feeding options for families under their care.…”
mentioning
confidence: 99%